2015
DOI: 10.1177/0962280215597716
|View full text |Cite
|
Sign up to set email alerts
|

Unbiased estimation for response adaptive clinical trials

Abstract: Bayesian adaptive trials have the defining feature that the probability of randomization to a particular treatment arm can change as information becomes available as to its true worth. However, there is still a general reluctance to implement such designs in many clinical settings. One area of concern is that their frequentist operating characteristics are poor or, at least, poorly understood. We investigate the bias induced in the maximum likelihood estimate of a response probability parameter, p, for binary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 42 publications
1
48
0
Order By: Relevance
“…The FLGI design results in a larger underestimation of the time trend coefficient. This underestimation is consistent with that observed in Villar et al for reasons clarified in Bowden and Trippa . The power to detect a significant time trend for the FLGI is more than halved compared to CR.…”
Section: Adjusting the Model For A Time Trendsupporting
confidence: 91%
“…The FLGI design results in a larger underestimation of the time trend coefficient. This underestimation is consistent with that observed in Villar et al for reasons clarified in Bowden and Trippa . The power to detect a significant time trend for the FLGI is more than halved compared to CR.…”
Section: Adjusting the Model For A Time Trendsupporting
confidence: 91%
“…As compared to fixed equal randomization, the BRAR is more likely to terminate trials early and has been shown to lead to inflated type I error and biased treatment estimates. [5][6][7][8][9][10][11] Having more subjects assigned to the better-performing arm may improve the efficiency to identify the superior treatment arm, depending on the model used for the efficacy analysis and success rate of the two treatments. However, in the presence of a time-trend, the For subjects in the arm without specific trend pattern, a random sampling is conducted among all treatment arm subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Altman et al studied the time-trend and suggested investigators to monitor the time-trend graphically [4].However, theresponse time-trend hasrarely been examinedin trial practice. The presence of a time-trend may bringbiasin treatment effect estimates, andinflate type I error [5][6][7][8][9][10][11][12].In order to better understandthe impact of time-trend, we incorporated a BRAR design into a previously completed randomized controlled phase 3 trial with a time-trend. The goal of this simulation study is to investigate drawbacks of using BRAR in the presence of time-trend, and to explore potential solutions to the problem.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have compared frequentist and Bayesian approaches in trial designs . However, it is, in general, far from straightforward to evaluate Bayesian adaptive designs using frequentist criteria, particularly when the Bayesian design is the solution of a decision theoretic optimization. In this paper, we propose a general simulation‐based approach to evaluate Bayesian adaptive designs in terms of frequentist criteria.…”
Section: Introductionmentioning
confidence: 99%